Multicriteria analysis of the assortment of innovative drugs in oncohematology as a tool for supporting decision-making in the field of drug provision - S. V. Nedogoda; A. S. Salasyuk; I. N. Barykina; V. O. Smirnova; E. A. Popova (Izdatelstvo OKI, 2018)
On the basis of multicriteria analysis, a pilot complex system for evaluating medicinal products (MP) used in the therapy of oncohematological diseases has been developed. The obtained results allow to rank MPs by priority of choice when making decisions on procurement of drugs or inclusion in MP lists in the framework of programs of preferential drug provision of the population. It has been shown that, according to the set of criteria, ibrutinib in treatment of chronic lymphocytic leukemia (CLL) has the highest priority, followed by obinutuzumab (CLL treatment) and ruxolitinib (treatment of myelofibrosis).